Deep Disagreement and Patience as an Argumentative Virtue - Phillips, Kathryn (Informal Logic, 2021)
During a year when there is much tumult around the world and in the United States in particular, it might be surprising to encounter a paper about patience and argumentation. In this paper, I explore the notion of deep disagreement, with an eye to moral and political contexts in particular, in order to motivate the idea that patience is an argumentative virtue that we ought to cultivate. This is particularly so because of the extended nature of argumentation and the slow rate at which we change our minds. I raise a concern about how calls for patience have been misused in the past and argue that if we accept patience as an argumentative virtue, we should hold people in positions of power, in particular, to account.